KẾT QUẢ CHỌN GIỐNG LÚA MTL149 Ở ĐỒNG BẰNG SÔNG CỬU LONG - Thái, Lê Xuân; Đệ, Nguyễn Ngọc (Tạp chí Khoa học Đại học Cần Thơ, 2004)
Abstract MTL149 has the original name: IR56381-139-2-2 which was tested preliminary observation in dry season of year 1991, replicated yield trial in wet season of year 1995 and region trial in dry season of year 1996. Then, it had selected for rice production in large scale in wet season of year 1996 và and dry season of year 1997. With good characteristics such as: short duration, strong tillering capacity, strong stem, high percentage of filled grains, and suitability for soils affected by acid sulfate or salinity, MTL149 had selected for rice production as one major rice variety in Kiengiang province. With seeding condition, duration of MTL149 has lasted 90-95 days and yield of which was about 6.6 ton/ha in reagion trial experiment. The height plant of MTL149 varied from 85 to 100 cm and the number of panicle of which varied from 342 to 370 panicles/m2. MTL149 had number of filled grains from 45 to 83 grains/panicle with 78 percentage of filled grain/panicle and 1000 grain weight of which was from 25.5 to 27.0 gam. Cereals Varieties Evaluation Committee of Agriculture and Rural Development Ministry inHo Chi Minh City certificated MTL149 as regional rice variety in April, 2004. Title: The result of rice selection of MTL 149 rice variety in the Mekong Delta